Advancing Casing Head Design on Wellhead Equipment Under Hydrostatic Pressure Using Finite Element Analysis - Putra, Deny Jaya; Hasibuan, Fardin; Liston, Sony; Hafiz, Abdul (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2025)
Ensuring the structural integrity of casing heads under high-pressure conditions is crucial in oil and gas well safety. This study applies Finite Element Analysis (FEA) using Solid-Works 2024 to evaluate a 13-5/8 5K × 13-3/8 5K casing head design under hydrostatic pressure up to 7,500 psi, following API 6A standards. Unlike conventional designs that rely on a single material, this research compares AISI 4130 alloy steel and Stainless Steel 410 to assess their structural performance and interchangeability. The simulation analyzed stress distribution and deformation, revealing both materials stayed well within safe limits, with a maximum Von Mises stress of 18,196 psi and deformation of 0.00006112 inch. The results demonstrate that material substitution is structurally viable, offering a cost-effective and supply-chain-resilient solution. The novelty lies in validating design adequacy through simulation of the weaker material, confirming its suitability for both. This method enhances design flexibility and material selection strategies for pressure-containing components.